The Development of a More Efficient Internal Tender Procedure Framework for Australian Construction Contractors - Urquhart, Stephen; Whyte, Andrew; Lloyd, Natalie (2017)
With increasing corporate governance requirements the nature of Australian construction contractors’ (CC) internal tender review procedures is changing. A research program is underway to determine the effectiveness and efficiency of such changes and whether they are producing improved CC business results. To facilitate this objective a better understanding of current CC tendering practices and procedures was sought through detailed semi-structured qualitative interviews with 18 CCs, including five of Australia's largest contractors. Drawing from these interviews and extracts of tender procedures provided by nine of the CCs, a new internal tender procedure qualitative flowchart is developed, running from prospect identification to contract award. Many CCs now spend more than 10% (some over 15%) of their tender period hours addressing their internal tender reviews due to increased involvement of legal, commercial, finance and risk departments. Many CCs advised their key tender focus is risk mitigation to avoid the company winning a potential loss making project rather than determining a tender winning 'mark-up' value. While providing greater insight into the inner workings of CCs’ internal tender procedures, the new tender process flowchart also enables CCs to benchmark their tender procedures against empirically researched current practice.